Purifying the Faith, Acting for Progress: Reinterpreting Muhammadiyah - Kim, Hyung-Jun (Al-Jami'ah: Journal of Islamic Studies, 2024)
This paper investigates Muhammadiyah, specifically exploring the intricate relationship between purification and social activism and addressing the interpretive challenges inherent in their connection. It posits that ijtihad and progress, fundamental to Muhammadiyah’s theological underpinnings, broaden the understanding of purification beyond mere adherence to the Scriptures, aligning purification with the necessity of adapting to contemporary developments. The initial sections of the paper analyze Suara Muhammadiyah to shed light on the organization’s early theological framework that seamlessly integrates purification, social activism, ijtihad, and progress. Subsequent sections, drawing on diverse research findings, explore the evolution of these concepts and their implementations throughout Muhammadiyah’s history. The paper concludes that the fusion of ijtihad and progress has fostered diverse approaches to purification, reflecting various cultural and social contexts. This synthesis has prevented stagnation in the realm of social activism and infused it with vitality and dynamism.[Tulisan ini mengkaji ormas Muhammadiyah, khususnya tentang hubungan rumit antara pemurnian dan aktivisme sosial serta penafsiran-penafsiran dalam hubungan keduanya. Studi ini mengemukakan bahwa ijtihad dan kemajuan, yang merupakan landasan teologis Muhammadiyah, memperluas pemahaman tentang pemurnian lebih dari sekedar ketaatan pada kitab suci, tetapi menyelaraskan pemurnian dengan kebutuhan untuk beradaptasi dengan perkembangan kontemporer. Bagian awal makalah ini menganalisis Suara Muhammadiyah, menyoroti kerangka teologis awal organisasi yang mengintegrasikan pemurnian, aktivisme sosial, ijtihad, dan kemajuan. Bagian selanjutnya mengeksplorasi evolusi konsep-konsep tersebut dan implementasinya sepanjang sejarah Muhammadiyah, dengan memanfaatkan beragam temuan penelitian. Makalah ini menyimpulkan bahwa perpaduan ijtihad dan kemajuan telah mendorong beragam pendekatan terhadap pemurnian, yang mencerminkan berbagai konteks budaya dan sosial. Sintesis ini telah mencegah stagnasi di bidang aktivisme sosial serta menanamkan vitalitas dan dinamisme di dalamnya.]